2022
DOI: 10.1007/s10877-022-00886-2
|View full text |Cite
|
Sign up to set email alerts
|

A novel smartphone app for blood pressure measurement: a proof-of-concept study against an arterial catheter

Abstract: Smartphones may provide a highly available access to simplified hypertension screening in environments with limited health care resources. Most studies involving smartphone blood pressure (BP) apps have focused on validation in static conditions without taking into account intraindividual BP variations. We report here the first experimental evidence of smartphone-derived BP estimation compared to an arterial catheter in a highly dynamic context such as induction of general anesthesia. We tested a smartphone ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…The second dataset is from a study at the Lausanne University Hospital (CHUV, Lausanne, Switzerland) in collaboration with the Geneva University Hospital (HUG, Geneva, Switzerland) [9] approved by the local ethics committee (CER-VD no. 2018-01656; NCT03875248 at ClinicalTrials.gov).…”
Section: Datasetsmentioning
confidence: 99%
“…The second dataset is from a study at the Lausanne University Hospital (CHUV, Lausanne, Switzerland) in collaboration with the Geneva University Hospital (HUG, Geneva, Switzerland) [9] approved by the local ethics committee (CER-VD no. 2018-01656; NCT03875248 at ClinicalTrials.gov).…”
Section: Datasetsmentioning
confidence: 99%
“…This BP estimation technique was subsequently migrated onto smartphone camera lenses to facilitate more common use. The smartphone application with the OptiBP TM was assessed in Switzerland against both arterial measurements recorded at the fingertips during general anesthesia 13 and reference auscultatory measurements based on the ISO 81,060-2:2018 standards. These studies demonstrated general concordance of OptiBP with reference measurements and highlighted performance gaps in estimating systolic arterial presure [13][14][15][16] .…”
Section: Introductionmentioning
confidence: 99%
“…The smartphone application with the OptiBP TM was assessed in Switzerland against both arterial measurements recorded at the fingertips during general anesthesia 13 and reference auscultatory measurements based on the ISO 81,060-2:2018 standards. These studies demonstrated general concordance of OptiBP with reference measurements and highlighted performance gaps in estimating systolic arterial presure [13][14][15][16] . While this research highlighted the potential of OptiBP, these assessments lacked independent evaluations in line with global validation standards and were conducted exclusively in high-income settings.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 This BP estimation technique was subsequently migrated onto smartphone camera lenses to facilitate more common use. The smartphone application with the OptiBP™ is being assessed in Switzerland against both arterial measurements during general anesthesia 13 and reference auscultatory measurements based on the ISO 81,060-2:2018 standards. [13][14][15][16] To ensure the accuracy of OptiBP™ across different environmental conditions and demographic pro les, we conducted a multi-site assessment study in Tanzania and Bangladesh among general populations, and in South Africa among a pregnant population.…”
Section: Introductionmentioning
confidence: 99%
“…The smartphone application with the OptiBP™ is being assessed in Switzerland against both arterial measurements during general anesthesia 13 and reference auscultatory measurements based on the ISO 81,060-2:2018 standards. [13][14][15][16] To ensure the accuracy of OptiBP™ across different environmental conditions and demographic pro les, we conducted a multi-site assessment study in Tanzania and Bangladesh among general populations, and in South Africa among a pregnant population. The inclusion of pregnant populations was particularly important to align with the study's key objective of assessing innovations to improve BP screening within routine antenatal care and management of hypertensive disorders of pregnancy.…”
Section: Introductionmentioning
confidence: 99%